2022
DOI: 10.3168/jds.2021-21105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed, farm intensiveness, and cow productivity on infrared predicted milk urea

Abstract: Milk urea content is receiving growing interest from science and industry as a tool to infer the protein adequacy of dairy cows' diets, nitrogen excretion and its environmental impact, and efficiency of animals' protein metabolism. Fourier-transform infrared (FTIR) prediction is a high-throughput method for rapidly and cheaply evaluating milk urea content at the population level. Existing knowledge of the major sources of variation (e.g., year, season, farming system, individual herd, and the cow's breed, pari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Total solids represent all milk constituents and can thus be used as an evaluation parameter for quality (Alessio et al, 2021). The decrease in MUN values in the SubG can be explained by the variable level of urea in the milk of the same herd of cows, for which the predisposing factors are age at first calving, number of lactations, stage of lactation, breed (Bittante, 2022), and energy and mineral imbalance caused by inflammation (Martins et al, 2021). Cows with lower metabolic conditions may have elevated milk urea levels, which are closely related to blood urea concentrations (DePeters et al, 1992;Gustafsson & Palmquist, 1993), suggesting that the elimination of urea, which requires energy, is impaired in cows with a low glycemic index (Gross et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Total solids represent all milk constituents and can thus be used as an evaluation parameter for quality (Alessio et al, 2021). The decrease in MUN values in the SubG can be explained by the variable level of urea in the milk of the same herd of cows, for which the predisposing factors are age at first calving, number of lactations, stage of lactation, breed (Bittante, 2022), and energy and mineral imbalance caused by inflammation (Martins et al, 2021). Cows with lower metabolic conditions may have elevated milk urea levels, which are closely related to blood urea concentrations (DePeters et al, 1992;Gustafsson & Palmquist, 1993), suggesting that the elimination of urea, which requires energy, is impaired in cows with a low glycemic index (Gross et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“… 13 measured MUN in 14 herds and found that MUN concentrations ranged from 11 to 23 mg/dL. In the measurement of MUN, Bittante 14 studied different breeds of dairy cows (Total 115819) and found that the mean value of MUN was 21.1 mg/dL. Currently, nitrogen wastage in dairy herds is more prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the physiological maturity of newborn animals depends on the physiological, biochemical and morphological status of the mother cow during the dry period, a change in which initiates the appearance of disorders in the functional system "mother-fetus", which affect the harmonious development of the fetus in a pregnant cow. Therefore, by correcting the vital processes in the body of dry cows, it is possible to increase the viability of newborn calves [37].…”
Section: Table 1 Advantages and Disadvantages Of Franchising For Fran...mentioning
confidence: 99%